A proposed protocol for acceptance and constancy control of computed tomography systems: A Nordic Association for Clinical Physics (NACP) work group report. (March 2013) - Kuttner, Samuel; Bujila, Robert; Kortesniemi, Mika; Andersson, Henrik; Kull, Love; Østerås, Bjørn Helge; Thygesen, Jesper; Tarp, Ivanka Sojat
Background: Quality assurance (QA) of computed tomography (CT) systems is one of the routine tasks for medical physicists in the Nordic countries. However, standardized QA protocols do not yet exist and the QA methods, as well as the applied tolerance levels, vary in scope and extent at different hospitals. Purpose: To propose a standardized protocol for acceptance and constancy testing of CT scanners in the Nordic Region. Material and Methods: Following a Nordic Association for Clinical Physics (NACP) initiative, a group of medical physicists, with representatives from four Nordic countries, was formed. Based on international literature and practical experience within the group, a comprehensive standardized test protocol was developed. Results: The proposed protocol includes tests related to the mechanical functionality, X-ray tube, detector, and image quality for CT scanners. For each test, recommendations regarding the purpose, equipment needed, an outline of the test method, the measured parameter, tolerance levels, and the testing frequency are stated. In addition, a number of optional tests are briefly discussed that may provide further information about the CT system. Conclusion: Based on international references and medical physicists' practical experiences, a comprehensive QA protocol for CT systems is proposed, including both acceptance and constancy tests. The protocol may serve as a reference for medical physicists in the Nordic countries.